PHYSICAL THERAPY MANAGEMENT FOR POST OP ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION KNEE SINISTRA (A CASE STUDY) - Syaiful, Azizah Ridha; Adnan Faris Naufal,; Siti Maryam, (Journal of Innovation Research and Knowledge, 2022)
The anterior cruciate ligament (ACL) is one of the four major ligaments that are important in stabilizing the knee joint. The ACL is easily at risk for injury, such as a rupture or tear. ACL occurs by contact or non-contact at the knee. Most injuries occur due to no-contact conditions almost 75% of cases. Mr. I was 16 years old on 2011 the patient injured his left knee while playing basketball. After that, there was so much pain around his left knee that he was unable to walk on his own. On October 29 2021, the patient underwent ACL and meniscus post-restructive surgery at the RSPI. After surgery, 1 week later the patient underwent physiotherapy at the Esa Unggul Sport Clinic, Jakarta. Patients undergo therapy four times in two weeks with a physiotherapy program that includes TENS, Quadriceps Set, Hamstring and Gastroc Stretching, Mobilization Exercises on the legs, Core exercise, Balance (passing ball), Exercises using Ankle. Patients were evaluated using antropometri, spygmomanometer, and goniometer. after 4 treatments the patient experienced a decrease in left knee edema, increased muscle mass, and increased contraction.